Japanese and ASEAN Security Strategies in Cyber Crime in 2021 - 2025 - Elsa Alviyani; Made Fitri Maya Padmi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Cybercrime cases have become an important issue in various countries, including Southeast Asia. This study discusses what ASEAN as an organization does to tackle cyber crime and develop cyber security by collaborating with other countries. This research is descriptive by using qualitative research methods through multilateral relations between Japan and ASEAN. The results of this study indicate that Japan has a contribution to help ASEAN countries strengthen cyber security by cooperating because both have the same interest in creating security and peace in Southeast Asia.